Advertising Business Pada Google AdSense di Youtube Perspektif Ekonomi Syariah - Fathudin Fathudin; Muhammad Mukromin (ITB AAS INDONESIA Surakarta, 2021)
Google AdSense is a service provider in the form of advertisements about products or companies which then work with publishers/bloggers as a place for advertising providers. Then every visitor who clicks on the ad the blogger will get paid from google AdSense. This study discusses the Advertising business on Google AdSense on Youtube from the perspective of Islamic Economics. The business is now a popular business among teenagers. The formulation of the problem is whether the advertising business on Google AdSense on YouTube is in accordance with Islamic Economics. The type of research used is field research. The results of the study show that the advertising business practices on Google AdSense on YouTube which are carried out between content creators or YouTubers are seen from the 'āqidain (union parties) and contract terms (ījāb and qabūl) are in accordance with sharia economic law, with a note on the type of advertisement. which will be displayed clearly the type and does not conflict with the Shari'ah'. Meanwhile, in terms of ma'qūd 'alaih (object of syirkah) there are differences of opinion between scholars, some allow it and some forbid it.